Accessibility of summer meals and the food insecurity of low-income households with children - Miller, Daniel P (Public health nutrition, 2016)
Almost no previous research has examined the impact of the US Department of Agriculture's (USDA) Summer Food Service Program and related Seamless Summer Option, which provide meals and snacks to low-income children over the summer. The present study investigated whether geographic accessibility of summer meals programme sites (a proxy for programme participation) was associated with food insecurity for low-income households. The study used data from the California Health Interview Survey (CHIS) and administrative data on summer meals sites in California. Geocoding was used to calculate driving time between CHIS households and nearby summer meals sites. Geographic accessibility was measured using a gravity model, which accounted for the spatially distributed supply of and demand for summer meals. Food insecurity and very low food security were measured using a standard six-item measure from the USDA. Low-income families with children (n 5394). A representative surveillance study of non-institutionalized households in California. Geographic accessibility was not associated with food insecurity. However, geographic accessibility was associated with a significantly lower probability of very low food security in the full sample and among households with younger children and those living in less urban areas. The USDA's summer meals programme may be effective at reducing the most severe form of food insecurity for low-income households with children. Expanding the number of summer meals sites, the number of meals served at sites and sites' hours of operation may be effective strategies to promote nutritional health over the summer months.